The Mountainous Ecosystems of the Western Frigian High Tell in Tunisia: Dynamics of the Population and Wastelands - Hamza Ayari (Revue de Géographie Alpine)
Wastelands, a feature that has prevailed predominately in the mountainous landscapes of the Tunisian High Tell in 2018, has been a source of conflicts between the residents and the forestall administration in the colonial and the national period since the end of the 19th century. Wastelands represent remaining ecological footprints on the landscapes of the Mediterranean hinterland due to the different forms of pressure on the forest ecosystems related to the population dynamics. Since the 19th century, the succession of the political and economic contexts has impelled the mountains population into movements of installations and waves of deforestation at high altitudes during their dislocation by the agrarian colonization, then in plains with equipment can only provide basic services. This fieldwork was guided by two questions:Did the abandonment, which led to land clearing, promote forest regeneration?Did the absentees’ ways of exploitation accelerate deforestation and erosion?It seems that the evolution of the wastelands has followed different paths in function based on the chronological abandonment and bioclimatic aptitudes of the ecosystems.